Ceratophorum helicosporum - a new for mycoflora of Turkey genus and species of hyphomycetes (Dematiaceae) - Huseyinov, E; Mel'nik, V; Selçuk, F (Mezhdunarodnaya Kniga, 2002)
Data on occurence of Ceratophorum helicosporum from leaves of Castanea sativa from Turkey (Rize Province) are presented.